2018
DOI: 10.1038/s41589-018-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of glycosylation sites by rapid synthesis and analysis of glycosyltransferases

Abstract: Glycosylation is an abundant post-translational modification that is important in disease and biotechnology. Current methods to understand and engineer glycosylation cannot sufficiently explore the vast experimental landscapes required to accurately predict and design glycosylation sites modified by glycosyltransferases. Here we describe a systematic platform for glycosylation sequence characterization and optimization by rapid expression and screening (GlycoSCORES), which combines cell-free protein synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
201
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 124 publications
(207 citation statements)
references
References 58 publications
6
201
0
Order By: Relevance
“…NGTs efficiently install a glucose residue onto asparagine side-chains within proteins using a uracil-diphosphate-glucose (UDP-Glc) sugar donor 24 . Importantly, NGTs are soluble enzymes that can be easily expressed functionally in the E. coli cytoplasm 22,25,26 . Because glycosylation systems using NGT for glycan-protein conjugation do not require protein transport across membranes or lipid-associated components, they have elicited great interest from the glycoengineering community for the production of recombinant protein therapeutics and vaccines 9,21,22,[26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…NGTs efficiently install a glucose residue onto asparagine side-chains within proteins using a uracil-diphosphate-glucose (UDP-Glc) sugar donor 24 . Importantly, NGTs are soluble enzymes that can be easily expressed functionally in the E. coli cytoplasm 22,25,26 . Because glycosylation systems using NGT for glycan-protein conjugation do not require protein transport across membranes or lipid-associated components, they have elicited great interest from the glycoengineering community for the production of recombinant protein therapeutics and vaccines 9,21,22,[26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent advances set the stage for this vision. First, the acceptor specificity of NGTs has been extensively studied using peptide and protein substrates 25,28 , glycoproteomic studies 25 , and the GlycoSCORES technique 26 . These studies revealed that NGTs modify N-X-S/T amino acid acceptor motifs resembling those in eukaryotic glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These examples include profiling lysine deacetylase (KDAC) specificities (Gurard-Levin, Kilian, Kim, Bahr, & Mrksich, 2010; Gurard-Levin, Kim, & Mrksich, 2009), as well as the substrate specificity of the protease OmpT (Wood et al, 2017). Additionally, we have used SAMDI and peptide arrays to optimize substrates for glycosyl transferases, and we have used carbohydrate arrays to discover new glycosyl transferase activities (Ban et al, 2012; Kightlinger et al, 2018). SAMDI peptide arrays are also compatible with measuring enzyme activities in cell lysates, as shown in a study observing distinct profiles of deacetylase activity associated with differentiation (Kuo, DeLuca, Miller, & Mrksich, 2013).…”
Section: Introductionmentioning
confidence: 99%